Pachyoliva columellaris G.B. Sowerby I, 1825 (Olividae, Caenogastropoda) in Peru: tidal migrations and population density - Winfried Peters (Revista Peruana de Biología, 2023)
The gastropod Pachyoliva columellaris (formerly Olivella columellaris) is particularly common on many sandy beaches in North Peru. In the studied region north of Paita, Piura province, the species reaches densities of over 80000 individuals per beach meter. The snails perform tidal migrations throughout the lunar cycle although tidal amplitudes differ four-fold between neap and spring tide. Not all animals complete their tidal migrations, and significant numbers remain above the water line at low tide. Throughout the tidal cycle, the proportion of small individuals is increased near the water line whereas large animals dominate in lower beach zones. I conclude that the sandy beaches north of Paita are well-suited for further studies of P. columellaris and the mechanisms underlying tidal migrations in invertebrates.